The Impact of Settlement Growth on Food Security Vulnerability: The Mediating Role of Rice Field Conversion and the Moderating Role of Agricultural Human Resource Capacity in Central Java - Rakhmawati, Anis; Atmaja, Hanung Eka; Ilmawan, Kurnia Fahmy (International Journal of Economics Development Research (IJEDR), 2025)
Settlement growth in Central Java Province continues to increase and intensify competition for land use with agricultural land, particularly rice fields. Uncontrolled rice field conversion has the potential to weaken the food production base and increase regional food security vulnerability. This study analyses the effect of residential growth on food security vulnerability with rice field conversion as a mediating variable and agricultural human resource capacity as a moderating variable in 35 districts/cities in Central Java. The study uses an explanatory quantitative approach based on secondary panel data for the period 2010–2021 (420 observations) with saturated sampling technique. The analysis was conducted using Partial Least Squares–Structural Equation Modelling (PLS-SEM) to evaluate the measurement model, test structural relationships, estimate indirect effects, and assess moderation effects through interaction constructs. The results show that settlement growth has a positive and significant effect on rice field conversion. Rice field conversion has a positive and significant effect on food security vulnerability and significantly mediates the effect of settlement growth on food security vulnerability. In addition, agricultural human resource capacity moderates the relationship between rice field conversion and food security vulnerability with a negative moderation direction (dampening effect), so that in areas with higher human resource capacity, the impact of rice field conversion in increasing food vulnerability tends to be weaker. These findings confirm that the impact of settlement growth on food vulnerability mainly occurs through land use change and can be mitigated by strengthening agricultural human resource capacity. The policy implications emphasise the need to integrate settlement growth control, protection of productive rice fields, and strengthening of agricultural human resource capacity through improving the quality of extension services and accelerating technology adoption to maintain the resilience of the food system in Central Java.